Phase Transition in Nanofluid of Platinum Above Room Temperature - Kumar, Virendra; Kumar, Jitendra; Chaudhary, A.K. (Asian Journal of Chemistry, 2011)
Nanofluids are attracting a great deal of interest with their enormous potential to provide enhanced performance properties, particularly with respect to heat transfer. Metal nanoparticles can be used in various application fields, such as optical filters or nanolithography. Platinum nanoparticles with narrow size distribution dispersed onto smooth, non-catalytic surfaces are of interest as model systems for the investigation of particle shape and size dependence of the catalytic activity of platinum towards reactions of interest in fuel cell systems. Measurement of ultrasonic velocity gives the valuable information about the physico-chemical behaviour of the liquid and liquid mixtures. Ultrasonic velocity is the velocity with which the ultrasound propagates through the material. It depends on material density and elasticity. It is related in a simple way to the various coefficients of compressibility, isentropic, isenthalpic and isothermal, hence the importance of its measurement and modeling in temperature and pressure ranges are widely used. Here we have measured the ultrasonic velocity at different temperature and frequencies of nanofluid of platinum using Interferometer technique and phase transition in the experimental temperature range has been discussed.